2012
DOI: 10.1590/s1516-35982012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros químicos, bioquímicos e mecânicos de fêmures de frangos de corte submetidos a diferentes balanços eletrolíticos

Abstract: Objetivou-se avaliar as características ósseas de frangos de corte tratados com diferentes níveis de balanço eletrolítico (BE) na ração. Foram criados 936 pintos de corte Cobb de 1 dia de idade distribuídos em delineamento de blocos ao acaso, com seis tratamentos (BE: -50, 0, 50, 100, 150 e 200 mEq/kg), seis repetições e 26 aves por unidade experimental. A ração basal para as duas fases - inicial, 1 a 21 dias, e de crescimento, 22 a 42 dias de idade - foi constituída de milho e farelo de soja, com balanço elet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
5
0
3
Order By: Relevance
“…Organic composition of bone was affected by the addition of the metabolite and NCPs exhibited an increasing linear response to the augmentation in active vitamin D 3 in the bones at 21 days of age. NCP content at 35 days was lower than at 21 days, which similar to the results obtained by Barbosa et al (2010) and Müller et al (2012) who reported a reduction in bone metabolic activity with an increase in age. NCPs work as nucleation points for the formation of hydroxyapatite crystals; osteocalcin, which acts as a chemoattractant for osteoclasts, is involved in the process of bone resorption (ROACH, 1994).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Organic composition of bone was affected by the addition of the metabolite and NCPs exhibited an increasing linear response to the augmentation in active vitamin D 3 in the bones at 21 days of age. NCP content at 35 days was lower than at 21 days, which similar to the results obtained by Barbosa et al (2010) and Müller et al (2012) who reported a reduction in bone metabolic activity with an increase in age. NCPs work as nucleation points for the formation of hydroxyapatite crystals; osteocalcin, which acts as a chemoattractant for osteoclasts, is involved in the process of bone resorption (ROACH, 1994).…”
Section: Resultssupporting
confidence: 90%
“…The mineral composition of bones may vary as it reflects the body's state of chemical equilibrium. Therefore, in cases of severe dysfunction, minerals (Na and K) are mobilized, leading to a change in their concentrations (MÜLLER et al, 2012). The maximum level of 1,25(OH) 2 D 3 added (2.5 µg/kg) did not affect the percentages of ash or minerals in the initial stage.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Na tabela 4 são apresentados os resultados dos índices de Seedor das tíbias e fêmures aos 60 e 90 dias de vida, onde não houve efeito significativo, dos níveis de cúrcuma, com ração em base o sorgo sobre este parâmetro em nenhum dos períodos avaliados, mesmo estas aves estando em pleno pico de postura. No que diz respeito à resistência óssea, os minerais cálcio e o fósforo, presentes na matriz inorgânica, dão rigidez ao osso e está intimamente relacionada à sua dureza e densidade mineral (MÜLLER et al, 2012;OLIVEIRA et al, 2014). Pereira et al (2012), apontam que devido a sua função de reserva mineral, os ossos são um tecido que possui a capacidade de movimentar, entrada e saída, de seus componentes minerais, essa disponibilidade pode ser mensurada pela densidade, utilizando o índice de Seedor como indicativo da densidade óssea, pois sabe-se que quanto maior o índice de Seedor, maior a densidade óssea e vice-versa.…”
Section: Resultsunclassified